A comprehensive review of drying meat products and the associated effects and changes - Mediani, Ahmed; Hamezah, Hamizah Shahirah; Jam, Faidruz Azura; Mahadi, Nursyah Fitri; Xi, Sharon Ying Chan; Rohani, Emelda Rosseleena; Che Lah, Noor Hanini; Azlan, Ummi Kalthum; Khairul Annuar, Nur Aisyah; Azman, Nur Aida Fatin; Bunawan, Hamidun; Sarian, Murni Nazira; et al. (Frontiers Media, 2022)
Preserving fresh food, such as meat, is significant in the effort of combating global food scarcity. Meat drying is a common way of preserving meat with a rich history in many cultures around the globe. In modern days, dried meat has become a well enjoyed food product in the market because of its long shelf-life, taste and health benefits. This review aims to compile information on how the types of meat, ingredients and the used drying technologies influence the characteristics of dried meat in physicochemical, microbial, biochemical and safety features along with technological future prospects in the dried meat industry. The quality of dried meat can be influenced by a variety of factors, including its production conditions and the major biochemical changes that occur throughout the drying process, which are also discussed in this review. Additionally, the sensory attributes of dried meat are also reviewed, whereby the texture of meat and the preference of the market are emphasized. There are other aspects and concerning issues that are suggested for future studies. It is well-known that reducing the water content in meat helps in preventing microbial growth, which in turn prevents the presence of harmful substances in meat. However, drying the meat can change the characteristics of the meat itself, making consumers concerned on whether dried meat is safe to be consumed on a regular basis. It is important to consider the role of microbial enzymes and microbes in the preservation of their flavor when discussing dried meats and dried meat products. The sensory, microbiological, and safety elements of dried meat are also affected by these distinctive changes, which revolve around customer preferences and health concerns, particularly how drying is efficient in eliminating/reducing hazardous bacteria from the fish. Interestingly, some studies have concentrated on increasing the efficiency of dried meat production to produce a safer range of dried meat products with less effort and time. This review compiled important information from all available online research databases. This review may help the food sector in improving the efficiency and safety of meat drying, reducing food waste, while maintaining the quality and nutritional content of dried meat.